AB0150 Sex-specific differences in cardiac involvement in ssc patients – relation to angiotensin and endothelin receptors and antibodies?. (23rd January 2014) - Adler, S.; Guenther, J.; Kill, A.; Becker, M.; Radic, M.; Siegert, E.; Riemekasten, G.
Abstract : Background: Autopsy studies showed cardiac fibrosis in the majority of patients with systemic sclerosis (SSc). Male SSc patients are at higher risk for left ventricular failure than their female counterparts suggesting sex-related differences in activation and migration of inflammatory cells into the heart leading to tissue fibrosis. Angiotensin II and endothelin-1 as well as activation of their specific receptors by autoantibodies (AB) may contribute to these abnormalities. This may depend on expression of angiotensin-II type-1 (AT1R) and endothelin-1 type-II (ETAR). Methods: In our single-center SSc data base cardiac involvement was evaluated by echocardiography and electrocardiogram (ECG) and defined by one abnormality either in ejection fraction (EF), in diastolic dysfunction or ECG changes. AB levels against AT1R and ETAR were measured by a commercially available ELISA in arbitrary units (AU, One Lambda, Inc., USA). Peripheral blood mononuclear cells (PBMC) from 8 healthy female and 6 healthy male as well as from 10 female and 8 male SSc patients were analyzed for AT1R and ETAR expression by flow cytometry. Statistics were performed using Mann-Whitney-test. Results: Clinical data for cardiac involvement were available for 623/733 SSc patients. Cardiac involvement was significantly more often present in male than in female patients (52/103, 50.5% males versus 154/520, 29.6% females, p< 0.0001). Overall 206/623 patients showed cardiac involvement with a male/female ratio for EF: 13%/7% (p=0.0105), diastolic dysfunction: 36%/29% (p=0.0514) and ECG: 27%/16% (p=0.0044). In cardiac disease mean AT1R AB were higher in male patients whereas ETAR AB were higher in female versus male SSc patients (not significant, n.s.). In patients without cardiac involvement mean levels of AT1R AB were higher in males than in females whereas ETAR AB did not differ between males and females (n.s.). AT1R and ETAR were expressed on all PBMC. In healthy individuals, males showed higher percentages of cells expressing AT1R and ETAR compared to females. Similar results were obtained for receptor density. In SSc patients, no sex differences in receptor expression were observed. Comparing healthy males to male SSc patients, AT1R density and the percentage of cells expressing AT1R were significantly reduced in nearly all PBMC subsets of male SSc patients. The percentage and density of T cells expressing ETAR were diminished, too. Conclusions: Sex-specific differences in clinical manifestations of cardiac involvement in SSc patients, in autoantibody levels against AT1R and ETAR, different expression of the receptors in healthy males versus females, as well as sex-specific differences in their activation status as reflected by more pronounced downregulation of the receptors in male patients suggest a possible contribution of AT1R/ETAR-mediated processes. Disclosure of Interest: None Declared